2020
DOI: 10.1007/s10948-020-05485-3
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Magnetocaloric Effect and Critical Behaviour in Ni50Mn30(Sn,In)20 Heusler Alloys

Abstract: A detailed investigation of structure, critical behaviour and magnetocaloric properties of Ni50Mn30Sn20 (Sn20) and Ni50Mn30In20 (In20) alloys has been investigated by means of Xrays diffraction and magnetic measurements. Ni50Mn30Sn20 alloy shows a cubic austenite 2 1 structure, and undergoes a second order magnetic transition at a Curie temperature of ,1 ( 20) = 333 . However, the Ni50Mn30In20 alloy exhibits a mixture of cubic 2 1 and 2 austenite structures having Curie temperatures of ,2 ( 20) = 285 and * ( 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“… 47 The critical exponents of these two DPs are shown in Table 2. In fact, this happens for various magnetic materials 43,48–51 . In general, such unusual phenomenon is often related to magnetic disorder, magnetic inhomogeneities, and the presence of the Griffith phase 43,48,51 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 47 The critical exponents of these two DPs are shown in Table 2. In fact, this happens for various magnetic materials 43,48–51 . In general, such unusual phenomenon is often related to magnetic disorder, magnetic inhomogeneities, and the presence of the Griffith phase 43,48,51 .…”
Section: Resultsmentioning
confidence: 99%
“…In fact, this happens for various magnetic materials. 43,[48][49][50][51] In general, such unusual phenomenon is often related to magnetic disorder, magnetic inhomogeneities, and the presence of the Griffith phase. 43,48,51 To clarify why the obtained exponents are inconsistent with common theoretical models, effective critical exponents in the asymptotic region need to be further investigated.…”
Section: Space Group Fm3mmentioning
confidence: 99%
“…Among all the above-mentioned materials, Ni-Mn-X (X = Sn, Sb, In, Ga) family depends on their composition and a minute change in composition can lead to significant effects. Although this family shows magneto-structural transformation most often, there have been many compositions which shows only magnetic transition [38][39][40]. It has been reported that, introduction of Co at the Ni site increases the ferromagnetic coupling, thus enhancing the MCE values in the process [41] and the brittleness of these alloys can be reduced significantly by substituting Fe at the Ni site, giving these materials mechanical stability [42,43].…”
Section: Introductionmentioning
confidence: 99%
“…Gd-based and Ni-Mn-In alloys are good candidates for magnetic refrigeration devices. Thus, Gd [12] or In [13] addition has been also analyzed. A minor amount of other metallic elements, such as Zn [14], Al [15] or Pd [16], or metalloids, such as B [17] have been also checked.…”
Section: Introductionmentioning
confidence: 99%